Beige Adipose Tissue Identification and Marker Specificity—Overview - Pilkington, Anna-Claire; Paz, Henry A.; Wankhade, Umesh D. (Frontiers in Endocrinology, 2021)
Adipose tissue (AT) is classified based on its location, physiological and functional characteristics. Although there is a clear demarcation of anatomical and molecular features specific to white (WAT) and brown adipose tissue (BAT), the factors that uniquely differentiate beige AT (BeAT) remain to be fully elaborated. The ubiquitous presence of different types of AT and the inability to differentiate brown and beige adipocytes because of similar appearance presents a challenge when classifying them one way or another. Here we will review the latest advances in BeAT, BAT, and WAT identification and compare several transcript markers described in the literature. The paper will highlight some of the difficulties these markers pose, and offers new perspectives on possible transcript-specific identification of BeAT. We hope that this will advance the understanding of the biology of different AT. In addition, concrete strategies to distinguish different types of AT may be relevant to track the efficacy and mechanisms around interventions aimed to improve metabolic health and thwart excessive weight gain.